Book Review: Towards a Maqasid al-Shariah Index of Socio-Economic Development; Theory and Application - Azzam, Hilmy Abdullah (SMART Insight, 2024)
The book Towards a Maqasid al-Shariah Index of Socio-Economic Development, edited by Salman Syed Ali, offers a new paradigm in measuring development based on the principles of Maqasid al-Shariah. This approach challenges the dominance of materialistic indicators like GDP by offering a comprehensive measure of human well-being, encompassing spiritual, moral, and social dimensions. The book introduces two main methodological approaches—the achievement approach and the deprivation approach—and proposes the Maqasid al-Shariah Index (MSI) as an alternative development index. Research across chapters demonstrates that integrating Islamic values can enrich development theory and lead to more just and sustainable economic policies.